1997
DOI: 10.1093/nar/25.18.3643
|View full text |Cite
|
Sign up to set email alerts
|

Mutation frequencies at codon 248 of the p53 tumour suppressor gene are not increased in colon cancer cell lines with the RER+ phenotype

Abstract: The replication-error positive (RER+) phenotype characterizes tumour cells with microsatellite instability. This 'mutator phenotype' is thought to induce spread mutations throughout the genome, thus increasing the risk of tumour development. Here we analyse spontaneously arising mutations at the tetranucleotide CCGG ( Msp I recognition site), at positions 14 067-14 070 of the p53 gene sequence, in three colon cancer cell lines, two with microsatellite instability and one without this characteristic. This restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
5
1
Order By: Relevance
“…We found concordance of p53 mutations and mismatch repair gene mutations in eight cases of secondary tumors. This is contrary to other studies showing that in tumors of the intestinal type, which had a germline mutation in an hMSH2 or hMLH1 gene, frequencies of mutation in adenomatous polyposis coli, p53, K‐ ras ‐2 genes, and LOH on tumor suppressor regions were extremely low 52–59. Moreover, the lack of instability or very rare microsatellite instability (1 of 54 samples) has been documented in primary pediatric brain tumors 31, 60.…”
Section: Discussioncontrasting
confidence: 67%
“…We found concordance of p53 mutations and mismatch repair gene mutations in eight cases of secondary tumors. This is contrary to other studies showing that in tumors of the intestinal type, which had a germline mutation in an hMSH2 or hMLH1 gene, frequencies of mutation in adenomatous polyposis coli, p53, K‐ ras ‐2 genes, and LOH on tumor suppressor regions were extremely low 52–59. Moreover, the lack of instability or very rare microsatellite instability (1 of 54 samples) has been documented in primary pediatric brain tumors 31, 60.…”
Section: Discussioncontrasting
confidence: 67%
“…We identified a mutation affecting amino acid 246 (R246H), which is considered equivalent to amino acid 248 in human p53, a known mutational hot spot. 69 Of interest, the GLI1 -expressing medulloblastoma cell line, Daoy, also carries a p53 mutation (C242F). 68 Together, this suggests that at least sometimes, p53 mutations may shift the balance toward dysregulated cell survival in GLI1 -expressing medulloblastomas and that during development functional interactions between GLI1 and p53 may maintain normal cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, well‐differentiated adenocarcinomas were significantly more likely to harbour a TP53 mutation than moderately or poorly differentiated carcinomas. Well‐differentiated carcinomas are associated with fewer genetic abnormalities than poorly differentiated carcinomas, 41 and it has also been shown that the presence of a TP53 mutation is inversely related to microsatellite instability and is associated with fewer other genetic abnormalities 35,42,43 . It is feasible that a TP53 mutation may result in neoplastic progression without the need for many other genetic insults, thereby resulting in the development of a well‐differentiated carcinoma.…”
Section: Discussionmentioning
confidence: 99%